British Election Study Combined Wave 1-13 Internet Panel - Fieldhouse, E; Green, J; Evans, G; Schmitt, H; van der Eijk, C; Mellon, J; Prosser, C (University of Oxford, 2018)
The British Election Study (BES) is one of the longest running election studies world-wide having taken at every general election since 1964. The BES explores why people choose to vote (or not) and why they support one party rather than another, as well as wider questions about political preferences, attitudes and behaviours. There have been a number of panel studies associated with different election cycles. The BES 2015 Internet Panel Study waves 1-13 covers the period February 2014 up until and including the 2017 General Election. The study includes boosted samples of Scottish and Welsh voters in the lead up to and in the immediate aftermath of the Scottish Independence Referendum in September 2014. The fieldwork was conducted by YouGov and includes responses from approximately 30,000 respondents at each wave, with regular top-tops to maintain a representative sample of eligible electors. The 2014-17 panel forms part of an on-going panel survey with waves that covers the 2014 European Elections, the 2015 and 2017 General Elections, the 2016 EU referendum, and local and regional elections during this period. Full details of the methodology and fieldwork are available in the technical report that accompanies the data release. Full details of the questionnaire can be found in the codebook which also accompanies the data release. See also: http://www.britishelectionstudy.com/get-started/#.WoqpGq5l_DA and http://doi.org/10.5255/UKDA-SN-8202-1